Inhibiting Factors in the Application of Risk Management at Hospital X Jakarta - Lestari Hernawati; Rr. Tutik Sri Hariyati; Hening Pujasari; La Ode Abdul Rahman; Hana Mutiasari; Harpendewisasmita Harpendewisasmita (CV. Syntax Corporation Indonesia, 2024)
Background: The risk management program will run well with commitment and good management. This study aims to describe the experience of nurse managers in implementing risk management in hospitals. Research methodology: this study used a descriptive qualitative approach. The data collection technique used Focus Group Interviews with 12 nurse managers consisting of 1 Sub Installation Head, 7 Unit Heads, and 4 Team Leaders. Interviews were carried out three times, and each implementation consisted of four participants. Analysis using thematic content and consolidation for reporting qualitative research (COREQ) was used as a guide to research reporting. The research found three inhibiting factors in implementing risk management: 1) Busyness, 2) Lack of knowledge, and 3) Lack of structured monitoring and evaluation. Conclusion: The active participation of nurse managers in implementing risk management is very influential in the successful implementation of risk management in hospitals. Good time management, increasing the level of knowledge, and supported by a systematic risk management monitoring-evaluation system means that risk management will be carried out well